Genetic and Developmental Insights into Dental Anomalies in Cleft Lip and Palate (Journal of Medical & Health Sciences Review, 2025)
Background: Cleft lip (CL), Cleft palate (CP) or cleft lip and palate (CL/P) are among the most widespread craniofacial birth defects, with an occurrence of 1 in 700 live births. In addition to the major facial deformity, individuals with the condition often exhibit dental anomalies that add complexity to functional, cosmetic, and life-long rehabilitation. Objective: This review aims to discuss clinical, genetic, and developmental insights about the dental anomalies associated with CL/P and its defining patterns and molecular pathways. Method: A narrative review with a semi-structured format was performed through the databases of PubMed, Scopus, and Google Scholar (2000-2024). Inclusion criteria included studies that evaluate dental anomalies in CL/P patients and its genetic or developmental basis. To identify similarities among the identified anomalies and the underlying mechanisms, the data were examined by themes. Results: Hypodontia was the most common finding with a prevalence rate of between 28 and 79 % with maxillary lateral incisors being more common on the cleft side. Hyperdontia was seen in as many as 73 % of patients, and enamel defects were present in over 90 % of certain groups, localized to the cleft area in both. Cleft severity and palatal involvement were very strongly associated with malocclusion, especially Class III. The genetic basis highlights MSX1-PAX9, FGFR1 signaling, TP63 variants, and WNT pathway modulators (WNT10A, AXIN2) as key regulators linking fusion and odontogenesis in the craniofacial region. Conclusion: The dental anomalies of the CL/P patients are a result of local tissue distraction beside some modal genetic factors. Their prevalence is so high that it prompts the importance of early, multidisciplinary intervention. The improvements in developmental genetics and stem cell biology present new opportunity to revise treatment approaches and enhance living quality of affected individuals.